The Role of Implicature in Humor on TikTok: A Pragmatic Examination of Jokes and Punchlines in Short-Form Videos - Narjis Audah Rashk ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study examines the application of implicature to create humor in Tik Tok and how the pragmatic model of Grice (1975) may be applied in the study. As Tik Tok has become a popular site of disseminating comic content in the short format, the transparency of the practical processes that govern humorous communication is only more beneficial to the researchers as well as the representatives of linguistics and digital media. The paper shows that the implicature or the claim that something is inferred on what has been verbalized is one of the key contributors to the production of humor on Tik Tok videos through the prism of Grice. By examining a varied range of humor sources, including skits, punchlines, and short acts, the study is sure to identify the pragmatic strategies employed by the creators in order to trigger laughter and entertainment. The evaluation of the validity of the implicature of creating humor is done using the combination of the qualitative and quantitative analysis of the Grice (1975) model approach on the individual examples and the general trends of the approach used throughout all the platform. The findings reveal the creative tools, developed by TikTok creators to appeal to audiences that underscore the importance of the practical principles in shaping the way funny content is produced, consumed, and shared. The study will also enable us to know more about humor as a challenging social and linguistic phenomenon along with its contribution to the theoretical debates within the field of pragmatics in online communication. Moreover, the lessons learned have practical implications to digital marketing, media creation, and social media content creation that will provide advice on how to maximize humor techniques and improve interactions with the audience.DOI: https://doi.org/10.54633/2333-024-057-009